PENGEMBANGAN MEDIA PEMBELAJARAN KARSISTEM BERBASIS QR-CODE GUNA MENINGKATKAN PEMAHAMAN KONSEP EKOSISTEM PADA SISWA KELAS V SD MUHAMMADIYAH 11 SEMARANG - Noval Lail Aditya (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Development of KARSISTEM Learning Media (Ecosystem Cards) Based on QR-Code to Enhance Concept Understanding of Grade V Students at Muhammadiyah 11 Semarang” The background of this research is based on interviews with the fifth-grade teacher, revealing that students show low enthusiasm during IPAS lessons because the teacher primarily uses textbooks. Additionally, the teacher rarely utilizes learning media, often relying on a lecture method for material explanation, which causes student boredom. During the learning process, students are allowed to use their mobile phones to support classroom learning. The aims of this research are to develop QR-Code based learning media called "Karsistem," to evaluate the acceptance of this media, and to implement it in the classroom. This study employs a Research and Development (RnD) method using the Borg and Gall model. The results of the material expert validation obtained a percentage of 100%, categorized as "very feasible," while the media expert validation yielded 93%, also categorized as "very feasible." The teacher acceptance questionnaire scored 96%, and the student response questionnaire received a score of 83%. The average concept understanding score of students initially at 38 improved to an average of 97 after using the "Karsistem" learning media. This indicates that the QR-Code based "Karsistem" learning media effectively enhances students' understanding of IPAS material. The conclusion of this research indicates that the development of this card media was conducted using the RnD method. The acceptance of the QR-Code based "Karsistem" media is significantly beneficial for teachers during the learning process, particularly for the Ecosystem material in grade 5, with a questionnaire result of 97% rated as "very practical." The implementation of the QR-Code based "Karsistem" media is easy for students to use, achieving an 82% acceptance rate. The media successfully improved the concept understanding of fifth-grade students at Muhammadiyah 11 Semarang, as evidenced by a pre-test average score of 38 and a post-test average score of 97. Recommendations from this research suggest that schools and teachers should create innovative and creative learning experiences and utilize technology effectively in education. The QR-Code based "Karsistem" media can be used well, but there are suggestions from students and validators that should be considered for future research, such as adding audio or video as supporting materials.